USIA PEREMPUAN MENIKAH DALAM AL-QURAN: ANALISIS HERMENEUTIKA DOUBLE MOVEMENT FAZLUR RAHMAN - A. Hanif, Muhammad; N, Abd. Muid; Nurbaiti, Nurbaiti (Institut PTIQ Jakarta, 2023)
There is a gap between Islamic law and positive law in Indonesia regarding the minimum age standards for women to marry. This gap appears contradictory when applied to Marriage Law no. 16 of 2019 concerning changes in the minimum age for women to marry from 16 years to 19 years. This change to the Marriage Law was carried out as a positive response from the government to answer increasingly complex socio-cultural demands. Meanwhile, Muslims in Indonesia are still guided by Islamic law, which only requires the age of puberty (15 years) as the age limit for marriage. This research aims to find the concept of marriage age in the Al-Quran and then contextualize it in the current phenomenon of women's marriage in Indonesia. This research uses the maudhûi interpretation method, conceptual thematic model and Fazlur Rahman's double movement hermeneutic approach. Data was obtained through library research, a type of qualitative research. The research results obtained show that the concept of age for women to marry is found in QS. An-Nisa'/4: 6 and QS. An-Nur/24: 32-33. The moral ideal of this verse is the age of marriage as a wise age. In the Indonesian context, the minimum age for women to marry is 19 years, and the ideal age is 25 years (the wise age)